Managing sustainable development through planning conditions - Johar, Foziah (Faculty of Built Environment, UTM, 2004)
Sustainable development has added to the range of issues included in the mediation of interests with which the planning system is engaged. It is indeed arguable that in the planning system the concept of sustainable development has been adopted more firmly on a statutory basis than in other field. This does not necessarily means that a systematic transformation of the planning agenda has occurred. Despite the improved development plan, the planning system is still underpinned by a presumption in favour of development which to some is a sign of inherent contradiction with sustainable development. Several areas of actions should therefore be considered in the local planning strategy to achieve a more radical approach to environmental sustainability. These include conservation, shaping the locational pattern of development and accommodating environmentally desirable qualities in all development. This paper considers the extent of local planning authorities through their development control powers fulfil this role. This paper examines the conditions which accompanied planning approval to determine the extent of control pertaining to environmental aspects. The results indicate the lack of consideration given to environmental related matters compared to the traditional concerns of land use planning. Finally the paper discusses the constraint of the present system and prospects to facilitate the achievement of sustainable development.